استراتيجيات وطرائق تدريس المهارات اللغوية لغير الناطقين باللغة العربية في ضوء نتائج البحوث التربوية - ترکی الملحم (مجلة ابحاث كلية التربية الاساسية, 2023)
The study aims to identify teaching language skills strategies and methods for non-Arabic speakers in the light of educational research results, classified them according to the axis of the educational process, this is done through digital databases and Arab libraries for research and educational thesis. The researcher uses the analytical method, prepares the analysis card and indicators for classifying teaching strategies and methods, and ensurs the validity and reliability of the analysis card. The sample of the study includes (268) researches and educational theses. It is found (66) teaching strategies appropriate for reading skill, (58) teaching strategies appropriate for writing skill, (53) teaching strategies appropriate for listening skill, and (82) strategies appropriate for teaching of speaking skill, and (28) appropriate teaching strategies for the four language skills (reading, writing, listening and speaking), The results of the study also reveal (71) teaching strategies appropriate for educational research based on the teacher, (74) teaching strategies based on the student, and (65) teaching strategies based on the student and the teacher. Finally, the study is ended with a number of recommendations and suggestions